G316(P) Chronic and complex care – a model for general paediatric leadership in a tertiary centre. (27th April 2015) - Evans, JA; Greenslade, R; Davis, P; Body, G; Van der Voort, J; Tuthill, D; Fish, R; Struik, S; Rogers, V; Norton, C; Powell, C
Abstract : Children with complex needs and their families coming into hospital with an acute admission may face a very unfamiliar environment despite perhaps having been under the care of community multidisciplinary teams for years. We have developed a General Paediatric model of care where one consultant is identified as the lead for hospital based care for each such patient. During admissions, day to day care is delegated to the attending general paediatric team, but the lead liaises with them and the family as needed, ensuring smooth communication and consistency between all specialties involved, maintaining a holistic overview. The lead continues to work with the family and community paediatrician post discharge and is involved in the development of advanced care planning focusing on management of symptoms and life threatening or life ending situations. Once a month the General Paediatric Consultant Meeting is devoted to chronic care inviting neonatology, community paediatrics and other specialists to identify patients who may require a lead and anticipating children who may be admitted to hospital in the near future. The lead ensures updated reports are in the patient notes and on the clinical portal. We use this meeting for peer support, sharing dilemma's and expertise. Since formalising this approach in 2013 forty two children have been allocated a Lead Paediatrician and discussed one or more times at the meetings. Providing trainees with experience in managing children with complex needs particularly, continuity of care, remains a challenge; this model provides a structured opportunity to experience this. Encouraging a trainee to identify such a patient and maintain contact with that patient and their lead is an excellent training opportunity. Standards of care for acute General Paediatrics are becoming well established but they do not exist for acute management of the complex care required by these patients. It is the aim of our group to develop an educational model as well as to contribute to the development of standards to ensure that this care is delivered well and is a properly resourced role for a General Paediatrician in a tertiary centre.